The Relationship Of Knowledge, The Role Of Health Personnel And Family Support With The Accuracy Of The Provision Of Mp-Asi In The Work Area Of The Sugih Waras Puskesmas In 2022 - Murdiyah Murdiyah; Andini Zuitasari; Erma Puspita Sari (Institute of Computer Science (IOCS), 2022)
Background: MP-ASI is a transitional food from breast milk to family food. The introduction and provision of MP-ASI should be done gradually, both in form and quantity, according to the ability of the baby. The provision of complementary feeding in sufficient quality and quantity is important for the rapid physical growth and development of children's intelligence during this period. Government Regulation No. 33 of 2012 concerning providing appropriate complementary foods (MP-ASI) from the age of 6 months and continuing breastfeeding until the age of 2 years. The application of this pattern of complementary feeding is at influencing the subsequent health status and improving the nutritional status of infants. Objective: This study aims to determine the relationship between knowledge, the role of health workers and family support with the accuracy of giving Mp-Asi in the Sugihh Waras Community Health Center Working Area in 2022. The population in this study were mothers who had babies aged 6-12 months who came to the Work Area of the Sugihh Waras Health Center. Incidental / Accidental Sampling. Results: The statistical results of the chi-square test obtained p value = 0.013 < 0.05, so it can be concluded that there is a relationship between knowledge and the accuracy of giving complementary foods, the statistical results of the chi-square test obtained p value = 0.170 < 0.05, so it can be concluded it was concluded that there was no relationship between the role of health workers and the accuracy of complementary feeding and the statistical results of the chi- square test obtained p value = 0.027 <0.05, so it could be concluded that there was a relationship between the role of health workers and family support for complementary foods. Conclusion: it can be concluded that there is a relationship between Knowledge and Family Support with the Accuracy of Giving MPASI at the Sugih Waras Health Center 2021 and there is no relationship between the Role of Health Workers with the Accuracy of Giving MPASI at the Sugih Waras Health Center 2021. Suggestion: